Development of a UPLC-MS/MS method for the therapeutic monitoring of L-asparaginase - Jeong, Hyeon-Cheol (Transl Clin Pharmacol, 2018)
This study aimed to develop a UPLC-MS/MS method for determining plasma levels of L-aspartic acid and L-asparagine and the activity of L-asparaginase. L-aspartic acid, L-asparagine, and L-aspartic acid-2,3,3-d(3) were extracted from human plasma by protein precipitation with sulfosalicylic acid (30%, v/v). The plasma samples were analyzed using an Imtakt Intrada amino acid analysis column with 25 mM ammonium formate and 0.5% formic acid in acetonitrile as the mobile phase with step gradient method at a flow rate of 0.5 mL/min. The injection volume was 5 µL, and the total run time was 15 min. Inter- and intra-batch accuracies (%) ranged from 96.62–106.0% for L-aspartic acid and 89.85–104.8%, for L-asparagine, and the coefficient of variation (CV%) did not exceed 7%. The validation results for L-aspartic acid and L-asparagine satisfied the specified criterion, however, the results for L-asparaginase activity assay showed a borderline validity. This study could be a foundation for further development of therapeutic drug monitoring systems using UPLC-MS/MS.